Desmodium spp. Development as Cover Crop Plant on Post Mining Land Reclamation - Nur Izzatil Hasanah (Jurnal Silvikultur Tropika, 2014)
Cover crop is a special plant to protect the soil from threats such as erosion damage and to improve soil physical and chemical properties. The purpose of this study is to measure soil cover crop plant productivity from Desmodium spp. species and to measure the impact of cover crop Desmodium spp. on the growth of jabon seedlings (Anthocephalus cadamba). This study was conducted in two stages, planting in the nursery to measure the plants growth and productivity and planting the cover crops along with jabon seedling to observe its effects to Jabon seedling. The acquired data then analyzed with SAS version 9.1. Study results shows that D. heterophyllum species has the highest seedling growth, productivity and growth rate compared with other Desmodium species. D. heterophyllum has the highest plant growth rate (LPT) up to 5.02 g/m2/day, while D. ovalifolium dan D. triflorum respectively 4.57 g/m2/day and 4.20 g/m2/day. Biomass production of D. heterophyllum also have the highest value compare with other Desmodium species, up to 122.52 g/m2, while D. ovalifolium dan D. triflorum respectively 92.79 g/m2 dan 52.08 g/m2. Desmodium spp. planting have significant effect on jabon seedling diameter growth, leaves count, and height thus recommended to be planted together.